2013
DOI: 10.1021/ja405925w
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Generation of Borenium Ions by Cooperative B–H Bond Activation: The Elusive Direct Electrophilic Borylation of Nitrogen Heterocycles with Pinacolborane

Abstract: The B-H bond of typical boranes is heterolytically split by the polar Ru-S bond of a tethered ruthenium(II) thiolate complex, affording a ruthenium(II) hydride and borenium ions with a dative interaction with the sulfur atom. These stable adducts were spectroscopically characterized, and in one case, the B-H bond activation step was crystallographically verified, a snapshot of the σ-bond metathesis. The borenium ions derived from 9-borabicyclo[3.3.1]nonane dimer [(9-BBN)2], pinacolborane (pinBH), and catecholb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(92 citation statements)
references
References 35 publications
4
85
0
2
Order By: Relevance
“…Recently, Oestreich, Tatsumi and co-workers developed a route to dehydroborate activated heteroarenes directly using pinacol-ligated borenium cations [73]. In contrast to previous studies using amine-ligated pinacol borenium cations that were ineffective for dehydroborations, they used a cationic Ru(II)-SR compound that was bound to [PinB] + through sulphur.…”
Section: Intermolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
“…Recently, Oestreich, Tatsumi and co-workers developed a route to dehydroborate activated heteroarenes directly using pinacol-ligated borenium cations [73]. In contrast to previous studies using amine-ligated pinacol borenium cations that were ineffective for dehydroborations, they used a cationic Ru(II)-SR compound that was bound to [PinB] + through sulphur.…”
Section: Intermolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
“…Obtaining insights into the turnover-limiting step and nature of catalyst deactivation pathways in this class of C−H functionalization reaction is crucial for the rational design of next generation catalysts. Information on the speciation of iridium, 17,18 ruthenium, 19 iron, 6a,d heterobimetallic copper, 6c,20 and frustrated Lewis pair (FLP) 21 catalysts in the presence of HBPin have been reported; however, the turnover-limiting step and possible catalyst deactivation pathways have not been identified, and principles for future catalyst development are not evident.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of chemical shift change in the 11 B NMR spectrum also ruled out formation of detectable amounts of sulfur-based borenium species. [33,34] This mechanistic control reaction demonstrated that demethylation of 1 is too slow relative to the timescale of the overall thioboration reaction (4 h) to be a step in the operative pathway and therefore ruled out the thiophilic activation pathway.…”
Section: Mechanistic Studies: Boron As a Thiophilic Or Carbophilic Lementioning
confidence: 98%
“…This lack of chemical shift change in the 11 B NMR spectrum also ruled out formation of detectable amounts of sulfur-based borenium species. [33,34] This mechanistic control reaction demonstrated that demethylation of 1 is too slow relative to the timescale of the overall thioboration reaction (4 h) to be a step in the operative pathway and therefore ruled out the thiophilic activation pathway.Next, two pathways were considered in which the ClBcat acts as a carbophilic Lewis acid by activating the C-C π system. [34] The first is through a haloboration/cyclization pathway proceeding through a chloroboration reaction analogous to that reported for alkynes, [30] generating intermediate 11 (Scheme 2, middle).…”
mentioning
confidence: 98%